2015
DOI: 10.1073/pnas.1500038112
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo imaging reveals differences between tectorial membrane and basilar membrane traveling waves in the mouse cochlea

Abstract: Sound is encoded within the auditory portion of the inner ear, the cochlea, after propagating down its length as a traveling wave. For over half a century, vibratory measurements to study cochlear traveling waves have been made using invasive approaches such as laser Doppler vibrometry. Although these studies have provided critical information regarding the nonlinear processes within the living cochlea that increase the amplitude of vibration and sharpen frequency tuning, the data have typically been limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 50 publications
9
145
0
2
Order By: Relevance
“…at frequencies around BF were observed in the guinea pig base (12), and similarly sized phase lags noted for TM re: BM motions in the mouse apex (13). A recent article by Lee et al (14), confirmed phase differences of fairly small magnitude at frequencies up to the BF.…”
Section: A Simple Schematic Modelsupporting
confidence: 54%
See 1 more Smart Citation
“…at frequencies around BF were observed in the guinea pig base (12), and similarly sized phase lags noted for TM re: BM motions in the mouse apex (13). A recent article by Lee et al (14), confirmed phase differences of fairly small magnitude at frequencies up to the BF.…”
Section: A Simple Schematic Modelsupporting
confidence: 54%
“…These response notches are likely caused by motions within the cochlear partition that excite OHCs. Measurements using optical coherence tomography (OCT) have observed differential motion between intracochlear structures (e.g., (12)(13)(14)), and cochlear models show that these different motions could be due to coupled traveling waves on the tectorial membrane (TM) and BM (15)(16)(17). The OCT results, as well as two-scala pressure measurements in scala media and ST, indicate fairly tightly coupling between TM and BM traveling waves (18).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the cochlea is characterized by values of the Reynolds number well below one; furthermore, the organ of Corti moves by only a very small fraction of its size [4]. Therefore, the nonlinearities originating from large deformations, which are important in most classical engineering problems involving flows, can be neglected here.…”
Section: Model Descriptionmentioning
confidence: 99%
“…However, the functional characteristics of the middle ear structures cannot be analyzed with conventional OCT. A newer variant of OCT, called phase-sensitive OCT, has been used by some research groups both in animal models, such as mice and chinchillas, to measure the vibration of the middle ear TM and the ossicles [20], as well as to assess the functionality of the inner ear (e.g. the cochlea) [21]. The vibrational amplitudes of the malleus and the incus through the TM in cadaveric human ears have also been measured with phase sensitive when a 0.5 kHz sound stimulus was used [22].…”
Section: Introductionmentioning
confidence: 99%